Molecular Characterization of Laboratory Reared Glossina palpalis palpalis and Glossina morsitans submorsitans Populations in Nigeria. Issue 2 (2016) - Orji, Christopher U; Onyeocha, Ignatius O; Shaida, Steven S; Dede, Peter M; Yakubu, Bitrus; Ella, Elijah E
No abstract available